2019
DOI: 10.22226/2410-3535-2019-4-382-385
|View full text |Cite
|
Sign up to set email alerts
|

On the prospects of using a phase transition in Ag nanoclusters for information recording processes

Abstract: To achieve a technological breakthrough in the creation of high-speed PCM cells, it is necessary to understand the nature of the switching effect of stable states and study the properties of the materials used for the working layer of a memory cell. The study of crystallization kinetics requires knowledge of the fundamental thermal properties of both crystal and amorphous states. If to consider all the chemical compounds tested for possible application in PCM memory, the metal nanoclusters of a relatively smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Currently an overwhelming majority of works in this field deal with multicomponent alloys. However a hypothesis [12,13] was put forward and proven, though only in a molecular dynamics experiment, that memory cells can be fabricated making use of phase change and stabilization in Ag nanoparticles. Molecular dynamics experiment [12,13] showed that very rapid (at approx.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently an overwhelming majority of works in this field deal with multicomponent alloys. However a hypothesis [12,13] was put forward and proven, though only in a molecular dynamics experiment, that memory cells can be fabricated making use of phase change and stabilization in Ag nanoparticles. Molecular dynamics experiment [12,13] showed that very rapid (at approx.…”
Section: Introductionmentioning
confidence: 99%
“…However a hypothesis [12,13] was put forward and proven, though only in a molecular dynamics experiment, that memory cells can be fabricated making use of phase change and stabilization in Ag nanoparticles. Molecular dynamics experiment [12,13] showed that very rapid (at approx. 20 TK/s rate) cooling of a liquid metallic nanoparticle to room temperature makes it amorphous whereas relatively slow cooling (at about 1 TK/s or lower rates) causes a crystalline transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ю.Я. Гафнер и его коллеги предполагают, что в роли элементов памяти могут выступать металлические наночастицы, например наночастицы Ag [26,27]. В этих работах было проведено МД моделирование наночастиц Ag и было установлено, что если охлаждение исходной расплавленной металлической наночастицы до комнатной температуры производится с очень высокой скоростью (порядка 20 ТК/с), то она переходит в аморфное состояние, тогда как при относительно более низкой скорости охлаждения (порядка 1 ТК/с и менее) -в кристаллическое.…”
unclassified
“…На основании этих результатов была выдвинута гипотеза о возможности создания элементов памяти, функционирующих за счёт изменения и последующего сохранения фазового состояния наночастиц серебра. Однако авторы работ [26,27] не привели соображений о том, как практически можно было бы обеспечить столь различную скорость охлаждения наночастиц, расположенных на расстоянии всего лишь в несколько нм друг от друга.…”
unclassified